Characteristics of patients with heart failure with preserved ejection fraction in primary care: Cross-sectional analysis - Forsyth, F; Brimicombe, J; Cheriyan, J; Edwards, D; Hobbs, R; Jalaludeen, N; Mant, J; Pilling, M; Schiff, R; Taylor, C; Zaman, MJ; Deaton, C (Royal College of General Practitioners, 2021)
Background Many patients with heart failure with preserved ejection fraction (HFpEF) are undiagnosed, and UK general practice registers do not typically record HF sub-type. Improvements in management of HFpEF is dependent on improved identification and characterisation of patients in primary care.